Discovery of novel steroidal histamine H 3 receptor antagonists/inverse agonists - Ledneczki, Istvan; Tapolcsányi, Pál; Gábor, Eszter; Éles, János; Greiner, István; Schmidt, Éva; Némethy, Zsolt; Kedves, Rita Soukupné; Balázs, Ottilia; Román, Viktor; Lévay, György; Mahó, Sándor (Bioorganic & medicinal chemistry letters, 2017)
Emerging from an HTS campaign, novel steroid-based histamine H-3 receptor antagonists were identified and characterized. Structural moieties of the hit compounds were combined to improve binding affinities which resulted in compound 4 as lead molecule. During the lead optimization due to the versatile modifications of diamino steroid derivatives, several in vitro potent compounds with subnanomolar binding affinities to histamine H-3 receptors were found. The unfavorable binding to rat muscarinic receptors was successfully reduced by tuning the basicity. Compound 20 showed significant in vivo activity in the rat dipsogenia model and could serve as a pharmacological tool in the future. (C) 2017 Elsevier Ltd. All rights reserved.